FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM REVITALISASI PERKEBUNAN SAWIT DI DESA TAPUNG JAYA KECAMATAN TANDUN KABUPATEN ROKAN HULU - Marlinawati "; Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Factors Affecting Implementation of Oil Palm Plantation Revitalization Program in the Village of Tapung Jaya Subdistrict Tandun Rokan Hulu District. Efforts to encourage the real sector through public welfare program is one of them through Oil Palm Plantation Revitalization Program. The purpose of this study is to is to determine the factors that affect the implementation of the Oil Palm Plantation Revitalization Program in the village of Tapung Jaya Subdistrict Tandun Rokan Hulu District. The concept of the theory is that researchers use public policy,public policy implementation and plantation revitalization program. This study used qualitative research methods to the assessment of descriptive data. In collecting the data, the researcher used interview techniques, observation and documentation. By using key informants as a source of information and analysis of the data using descriptive qualitative method. The results of this study indicate that the factors that influence Revitalization Program Implementation in Oil Palm Plantation Village of Tapung Jaya Subdistrict Tandun Rokan Hulu District is still a lack of clarity of the information received by the program managers , as well as the lack of facilities to support the implementation of the program, incentives are still less , and participation of the community as the target program is not maximized so that the implementation of the Oil Palm Plantation Village Revitalization in the village of Tapung Jaya Subdistrict Tandun Rokan Hulu District has not run optimally .Key Word: Public Policy, Implementation, Plantation Revitalization Program.